PREVALENCE OF DENTOALVEOLAR ANOMALIES IN 6-16 YEARS CHILDREN ACCORDING TO RETROSPECTIVE DATA ANALYSIS - Sh, Olimov S.; S.A, Gaffarov; R.K, Yakubov; A.A, Saidov; B.B, Badriddinov (International Journal of Psychosocial Rehabilitation, 2020)
It was studied the prevalence of dental anomalies at 6-9 years’ children in Bukhara region by carried out a comparative retrospective analysis of 831 cases histories of patients with various occlusion abnormalities for 2009- 2019 years. Distal occlusion and orofacial dysfunctions was diagnosed at 47,1% of all children. Number of children without orofacial dysfunctions and dentoalveolar anomalies remains almost unchanged (p> 0,10), whereas a share of children with dentofacial anomalies and deformities were increased from 16,5% to 72,6% (p <0.001), and children with orofacial dysfunctions without of dentoalveolar anomalies signs — reduced from 66,5% to 8,4% (p <0.001). Thus, orofacial dysfunctions had a high prevalence during the period of primary occlusal changes. It should be noted that one of the listed orofacial dysfunction in an isolated form was extremely rare. Most children had several dysfunctions. It follows that the correction of the orofacial dysfunctions should be carried out in an integrated manner.